Eficácia gerencial de sistemas de medição de desempenho: um estudo em uma organização pública policial - (:unkn) unknown (Universidade Federal do Pampa, 2024)
When designing and using Performance Measurement Systems (PMS), organizations do more than create, monitor, and evaluate result and performance metrics, they promote changes in various aspects of the organization. This reflects in the Managerial effectiveness of performance measurement (MEPM). To analyze the factors associated with dysfunctions, challenges and best practices, which explain the MEPM, of a public police organization, the study aimed to describe the PMS used by the organization; identify and describe the occurrence of dysfunctions, challenges, and best practices in the PMS; estimate the influence of dysfunctions, challenges, and good practices on the managerial effectiveness of the PMS; and propose a theoretical-empirical model for the Managerial effectiveness of performance measurement in a public police organization. Descriptive-explanatory research was carried out using the Survey method. The questionnaire data collection took place in 2024, with employees of a public federal police organization. The data were analyzed using multivariate statistics. The exploratory factor analysis by principal components explained 64.6% of the variance and retained two factors, linked to the challenges and dysfunctions used as independent variables: Goal displacement and Top-down implementation of the PMS, with significant factor loadings and unidimensional reliability along with the presence of good performance management practices. As a dependent variable, a reliable MEPM multiple scale was used. The regression model indicated a significant explanation (R²=50.4%) of the MEPM. There is empirical evidence that the factors linked to the top-down implementation of the PMS (β=-1.617) and goal displacement (β=-1.040), negatively influence the managerial effectiveness of the PMS. Data also demonstrates that best practices linked to PMS in public police organizations positively influence (β=2.25) MEPM. In turn, the comparison of regression model indicates the lack of moderation of best practices for the other dependent variables. The empirical support of the research hypotheses contributes to the theory of measuring public organizational performance, as it identifies and describes the degree of occurrence of some characteristics aimed at measuring performance in specific situations in the case of a police organization. Public organizations can encourage the use of best practices aimed at mitigating the negative effects of PMS challenges and dysfunctions. Furthermore, by identifying the most influential predecessors, organizations can try to control such factors to increase effectiveness in measuring public service performance.
Managerial effectiveness of performance measurement systems: a study in a public police organization
Keywords: Medição de desempenho; Eficácia gerencial; Análise fatorial exploratória; Regressão linear múltipla; Performance measurement; Managerial effectiveness; Exploratory factor analysis; Multiple linear regression; CNPQ::CIENCIAS SOCIAIS APLICADAS